Fostering access to and use of contextualised knowledge to support health policy-making: lessons from the Policy Information Platform in Nigeria - Chigozie Jesse Uneke; Etienne V. Langlois; Henry C. Uro-Chukwu; Jeremiah Chukwu; Abdul Ghaffar (BMC, 2019)
Abstract Background Contextualising evidence to inform policy-making is increasingly recognised as key to developing and implementing effective health policies. Creating a one-stop shop for evidence is an approach that can facilitate timely access to the best evidence to inform policy decisions. We report outcomes after implementation of the Policy Information Platform (PIP), a pilot one-stop evidence repository in Nigeria designed to alleviate barriers to accessing policy-relevant knowledge. Methods This cross-sectional study involved five phases, namely (1) consultation with Nigerian policy-makers to identify priority policy issues, areas of health policy information needs, and challenges and capacity constraints in accessing evidence for policy-making; (2) a stakeholder engagement workshop to formally launch the PIP; (3) extraction of data and other information from scientific articles, policy briefs, evaluation reports, grey literature and health policy documents relevant to policy-making in Nigeria (identified by Google and PubMed searches and by examination of websites of relevant Nigerian government ministries, agencies and parastatals), for use in developing the PIP website; (4) promotion of the PIP in national and state health policy meetings; and (5) evaluation of the PIP using a stakeholder survey questionnaire distributed via email and critical appraisal of the grey literature included in the PIP using the authority, accuracy, coverage, objectivity, date and significance (AACODS) checklist. Results Priority policy areas identified by policy-makers were disease control and prevention, population health issues and health administration. Challenges identified by policy-makers were a lack of adequate capacity to access policy-relevant evidence and transform the evidence into policy. Policy-makers suggested using systematic reviews, policy briefs and rapid response mechanisms and involving policy-makers in research as ways of increasing evidence uptake for policy. A total of 126 policy-relevant, peer-reviewed scientific articles, 85 health policy documents and 201 policy-relevant grey literature documents were selected for inclusion in the PIP. Of the 195 individuals contacted via email to evaluate the PIP, 31 (15.9%) provided a response. Respondents noted that the PIP facilitated access to information based on local evidence and context-sensitive data. Barriers identified included lack of knowledge about the PIP and limited capacity of end-users to use the data compiled in the platform. Conclusion An easily accessible one-stop shop of policy-relevant evidence can considerably improve policy-makers' access to evidence for use in policy-making and practice.